Application Of Fast Events In Sharia Economic Dispute Resolution Based On Supreme Court Regulation Number 14 Of 2016 In The Perspective Of Easy Of Doing Business - Rian Fauzi Rahman; Anita Afriana; Hazar Kusmayanti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to determine the comparison of conventional procedural lawsuits and simple event lawsuits for sharia economic dispute settlement based on Supreme Court Regulation Number 14 of 2016 concerning Procedures for Resolving Sharia Economic Disputes. This research refers to the perspective of Easy of Doing Business or ease of doing business to the extent of its contribution to improving the ranking of ease of doing business that has been indicatored, especially in Indonesia. The government has made regulations to provide business protection, among others, through legal certainty and ease of doing business. Various problems in the arrangement regarding the dispute resolution process are sufficient to make business actors reluctant to continue their business activities, from the length of the series of judicial methods, expensive costs, to the very confiscated time. This research uses normative juridical research methods carried out with research events on applicable positive legal principles or doctrines, research on legal systematics that can be carried out on certain laws and regulations or written which aims to identify the main understanding / basis of rights and obligations, legal events, legal relationships, legal objects that review Supreme Court Regulation Number 14 of 2016 concerning Procedures Sharia Economic Case Settlement in support of Easy Of Doing Business (EoDB) in business dispute cases with its resolution through a simple court system. The conclusion of this study is that the simple event lawsuit system in sharia economic disputes has been effectively applied in its application, which can be considered to have implications for the ease of doing business including starting business and enforcement contracts.